2016
DOI: 10.1007/s13193-016-0520-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Axillary Ultrasound, Fine Needle Aspiration Cytology and Sentinel Lymph Node Biopsy in clinically N0 Breast Cancer

Abstract: This study evaluates the combined role of axillary ultrasound, fine needle aspiration cytology and sentinel lymph node biopsy in clinically N0 axilla. Between January 2014 and June 2015, 150 women with early breast cancer underwent axillary ultrasound as a first investigation for nodal status. Suspicious nodes were subjected to image guided fine needle aspiration cytology. Non-suspicious and fine needle aspiration cytology negative axillary nodes proceeded to sentinel lymph node biopsy at time of primary breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Mastectomy was done in 77.1% cases and wide local excision in 22.9% cases. [14][15][16][17] Present study found that most common carcinoma observed on tumor histology was ductal carcinoma followed by lobular carcinoma. Another carcinoma like tubular, medullary, mucinous, papillary and mixed were also observed.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…Mastectomy was done in 77.1% cases and wide local excision in 22.9% cases. [14][15][16][17] Present study found that most common carcinoma observed on tumor histology was ductal carcinoma followed by lobular carcinoma. Another carcinoma like tubular, medullary, mucinous, papillary and mixed were also observed.…”
Section: Resultsmentioning
confidence: 56%
“…15 Goel et al observed 73.3% patients with invasive ductal carcinoma, 10% with invasive lobular carcinoma and 16.7% with other histologies (invasive tubular, medullary, mucinous, papillary, and mixed carcinoma) in their study. 16 Study done by Mainiero et al noted 191 invasive ductal carcinomas, 16 invasive lobular carcinomas, 13 with mixed invasive ductal and lobular carcinoma, and two invasive papillary carcinomas. 17 Present study noted most common tumor grade according to MBR system was grade II followed by grade I.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations